That was Then, This is Now - Gershon, Ilana; Ensmenger, Nathan; Carlson, Gordon; Deuze, Mark (AoIR Selected Papers of Internet Research, 2013)
This panel begins with a thought exercise. Each panelist has chosen a classic text from their home discipline and asks: what would happen if the author of that text revisited that topic today, using tools, techniques, or perspectives shaped by recent innovations in information technology and the digital humanities? We build on a question that one of our panelists, the historian of computing Nathan Ensmenger, asks in his article “The Digital Construction of Technology: Rethinking the History of Computers in Society,” about Bruno Latour's ground breaking ethnography of scientific practice, Laboratory Life. If Latour were to revisit the Salk Institute, what would he make of the pervasive presence of computers, computer-based instruments, and computational metaphors? How would this change the ways in which he did his research, his interpretation of the role of (increasingly digital) inscription devices, or his conclusions about the ways in which social interaction shapes the formation of scientific knowledge? Each of our panelists will perform a similar thought experiment as a starting point for thinking about the historical transformations happening both to one's object of analysis and to the practice of scholarship in the Internet era.